Behavioral Biases, Digital Payment Adoption, and Personal Financial Planning: Evidence from Millennial and Gen Z Consumers - M. Makhrus Ali; Abdul Manap; Suroso; Vidya Ramadhan Putra Pratama (Journal Management & Economics Review (JUMPER), 2026)
The rapid growth of digital payment systems has transformed financial behavior among younger generations, particularly millennials and Generation Z (Gen Z). While digital payments offer convenience and efficiency, their widespread adoption raises concerns regarding behavioral influences and personal financial planning. This study examines the relationships among behavioral biases, digital payment adoption, and personal financial planning among millennial and Gen Z consumers. Using a quantitative research design, data were collected through a structured survey of 320 respondents who actively use digital payment services. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test direct, mediating, and generational effects. The results indicate that behavioral biases significantly and negatively affect personal financial planning, while positively influencing digital payment adoption. Digital payment adoption is also found to have a significant negative effect on personal financial planning and partially mediates the relationship between behavioral biases and financial planning. Furthermore, multi-group analysis reveals that these negative effects are stronger among Gen Z consumers compared to millennials. These findings contribute to the behavioral finance and fintech literature by highlighting the psychological mechanisms through which digital payment systems influence financial planning. Practically, the study emphasizes the need for behavioral-based financial education and digital payment design features that promote mindful spending and long-term financial discipline among younger generations.